A meta-analysis suggests the association of reduced serum level of vitamin D and T-allele of Fok1 (rs2228570) polymorphism in the vitamin D receptor gene with celiac disease - Shree, Tanya; Banerjee, Pratibha; Senapati, Sabyasachi (Frontiers in Nutrition, 2023)
Purpose: As an immune-modulator vitamin D is known to regulate immune response and is implicated in disease pathogenesis. Celiac disease (CD) is a systemic autoimmune disease and susceptibility conferred by vitamin D metabolism is under investigation. Studies on the association of vitamin D metabolism and genetic polymorphisms are expected to explain the CD pathogenesis. We performed a systematic review based meta-analysis to investigate the 25(OH)D serum levels and susceptibility conferred by the genetic variants of VDR in CD. Methods: Systematic review was conducted through web-based literature search following stringent study inclusion-exclusion criteria. The Newcastle-Ottawa Scale and GRADE tools were used to assess the quality of evidence in studies and the study outcome. Cohen’s κ value was estimated to access reviewer’s agreement. RevMan 5.4.1 was used to perform the meta-analyses. Weighted mean difference and Meta p-value was assessed for 25(OH)D serum levels. Meta-odds ratio and Z test p-value were evaluated to estimate the allelic susceptibility of VDR variants. Results: 8/12 studies were evaluated for “25(OH)D” serum level while four studies were found eligible for SNPs (Bsm1, Apa1, Fok1 and Taq1) of VDR. Significantly higher level [WMD=5.49, p<0.00001] of 25(OH)D was observed in healthy controls than in CD patients. rs2228570-T (Fok1) [Meta-OR=1.52, p=0.02] was confirmed to be predisposing allele for CD. Conclusion: Reduced serum level of 25(OH)D and association of Fok1 T-allele of VDR confirmed in this study plays critical role in immunomodulation and maintaining barrier integrity which is majorly implicated in CD.